2006
DOI: 10.1007/s00464-005-0839-5
|View full text |Cite
|
Sign up to set email alerts
|

Distal pancreas surgery: outcome for 19 cases managed with a laparoscopic approach

Abstract: The authors can affirm that laparoscopy for the distal pancreas is a successful procedure in terms of results and surgical feasibility. Prospective studies are necessary to confirm their positive impression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 15 publications
3
20
0
Order By: Relevance
“…[14] Velanovich et al [36] reported a rate of POPF of 13% in both groups, whereas Kooby et al [37] reported 26% POPF in LDP and 32% in ODP. Another series showed 14% POPF in LDP (n = 70) vs. 13% after open surgery (n = 45), similar to the report of Corcione et al [38] (10.4% in LDP). In contrast, Fox et al [39] reported a higher incidence of POPF in LDP (28.57%) compared to ODP (13.16%), but LDP led to only grade A fistulae, while all the grade B-C fistulae occurred in the ODP group.…”
Section: Discussionsupporting
confidence: 84%
“…[14] Velanovich et al [36] reported a rate of POPF of 13% in both groups, whereas Kooby et al [37] reported 26% POPF in LDP and 32% in ODP. Another series showed 14% POPF in LDP (n = 70) vs. 13% after open surgery (n = 45), similar to the report of Corcione et al [38] (10.4% in LDP). In contrast, Fox et al [39] reported a higher incidence of POPF in LDP (28.57%) compared to ODP (13.16%), but LDP led to only grade A fistulae, while all the grade B-C fistulae occurred in the ODP group.…”
Section: Discussionsupporting
confidence: 84%
“…In most cases complete tumour resection preserving as much pancreatic tissue as possible is the treatment of choice [2,3]. Laparoscopic distal pancreatectomy (LDP) is recently recommended in adult patients with benign tumour of the pancreas body and tail [4,5]. We report our experience with two cases of LDP in children with Frantz tumour.…”
Section: Introductionmentioning
confidence: 99%
“…As familiarity developed, significant experiences were reported. Naturally, higher-volume centers have offered direct comparisons of laparoscopic and open outcomes [6,7,11,14,16,[21][22][23][24][25][26][27]. Over the past year, five reports have advanced this literature by pooling such studies using meta-analytical techniques [28, 29 • , 30, 31, 32 • ].…”
Section: Meta-analyses Comparing Laparoscopic and Open Distal Pancreamentioning
confidence: 99%
“…The feasibility of laparoscopic pancreatic surgery was first documented in numerous case series largely conducted at single institutions [4][5][6][7][8][9][10][11][12][13][14][15][16][17]. As familiarity developed, significant experiences were reported.…”
Section: Meta-analyses Comparing Laparoscopic and Open Distal Pancreamentioning
confidence: 99%
See 1 more Smart Citation